Reflective Practice and Frame Theory in Educational History: A Communicative Narrative Research Proposal - Rosser, Pablo; Seila Soler (Indonesian Journal of Education and Social Sciences, 2024)
This document presents a research proposal on the relationship between media and public perception regarding education. It is proposed, following Foster's tenets on the use of methodological pragmatism, to analyze narratives present in historical media and other educational documentation to comprehend how discourses are constructed through the narrative frames employed by the media and how this might influence the public's perception and understanding of educational issues. The proposed methodology is grounded in reflexive and critical analysis of existing literature, employing mixed qualitative and quantitative analysis techniques. Additionally, the use of reflective practice methods and frame theory is suggested to develop a scientific analysis from historical documents. This research aims to gain a more comprehensive insight into educational practices and debates within a specific period, thereby enabling a broader and more objective understanding and evaluation of the predominant educational discourse of the time.